2017
DOI: 10.1021/acs.inorgchem.6b01929
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Lithiated Diphosphanes R2P–P(SiMe3)Li (R = tBu and iPr) with [MeNacnacTiCl2·THF] and [MeNacnacTiCl3]. Formation and Structure of TitaniumIII and TitaniumIV β-Diketiminato Complexes Bearing the Side-on Phosphanylphosphido and Phosphanylphosphinidene Functionalities

Abstract: β-Diketiminate complexes of Ti-containing phosphanylphosphido ligands [NacnacTi(Cl){η-P(SiMe)-PR}] (Nacnac = [Ar]NC(Me)CHC(Me)N[Ar]; Ar = 2,6-iPrCH) were prepared by reactions of [NacnacTiCl·THF] with lithium derivatives of diphosphanes RP-P(SiMe)Li (R = tBu, iPr) in toluene solutions. Surprisingly, reactions of [NacnacTiCl·THF] with RP-P(SiMe)Li in THF solutions led to Ti complexes containing phosphanylphosphinidene ligands [NacnacTi(Cl)(η-P-PtBu)] via an autoredox path involving a migration of a nitrene NAr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 78 publications
(134 reference statements)
5
27
0
Order By: Relevance
“…The P–P distances in the phosphanylphosphido ligands in both complexes (2.198(2) Å – 2.2139(13) Å) are located in the range of single P–P bond and are comparable to distances in complexes with monodentate coordination of phosphanylphosphido ligands to the metal center. [2b], [5a]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P–P distances in the phosphanylphosphido ligands in both complexes (2.198(2) Å – 2.2139(13) Å) are located in the range of single P–P bond and are comparable to distances in complexes with monodentate coordination of phosphanylphosphido ligands to the metal center. [2b], [5a]…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of the –SiMe 3 on the phosphido phosphorus atom provides a possibility of reactivity studies. The phosphanylphosphido [ RR ′P‐P(SiMe 3 ); R = t Bu, i Pr; R ′ = t Bu, i Pr, Ph] complexes have been only obtained for early and middle transition metals: titanium, iron, hafnium, zirconium, molybdenum, and tungsten so far. Moreover, it should be emphasized that all reported works of metal complexes with RR ′P‐P(SiMe 3 ) moiety present only the mononuclear forms.…”
Section: Introductionmentioning
confidence: 99%
“…Auxiliary ligands that are strong π acceptors render electrophilic properties; auxiliary σ donors enhance the nucleophilic properties , . Our research group has been mainly focused on the synthesis, and recently, on the reactivity, of complexes with phosphanylphosphinidene ligands (R 2 P–P) . These compounds can be roughly considered as a subclass of phosphinidene complexes (RP), but they often exhibit significant differences in structure and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…While the NacNac family of ligands derived from 2,6‐disubstituted anilines (e. g. 2,6‐diisopropylaniline) have played major role in the development of low‐valent main group and transition metal chemistry,,,, TBZ which is double of 2,6‐diisopropylaniline can in principle form compounds that incorporate multiple NacNac units. Accordingly, the reaction of TBZ with acetylacetone was carried out under different reaction conditions, owing to very poor reactivity of the highly hindered amine, to isolate products 10 and 11 .…”
Section: Resultsmentioning
confidence: 99%
“…The benzidine core shows two sets of signals for the isopropyl groups and the aromatic protons, confirming the indole ring formation on only one end of the benzidine. Through the absence of signal due to -NH 2 group in the 1 H NMR spectrum of 13, it can be concluded that (2), C(6)-N(1) 1.430(2), N(1)-C(1)-C(2) 121.38 (16), N(1)-C(1)-C(4) 117.44 (14), C(2)-C(1)-C(4) 121.18 (16) 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 the indole formation has taken place on both ends of the benzidine molecule ( Figure S26). The resonances of the aromatic protons of the benzidine ring are downfield shifted compared to the resonance of aryl protons of TBZ.…”
Section: Comp Ortep Diagrams Selected Bond Lengths [å ] and Angles [mentioning
confidence: 98%